1987
DOI: 10.1056/nejm198702123160701
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cerebral Glucose Metabolism in Asymptomatic Subjects at Risk for Huntington's Disease

Abstract: Symptomatic patients with Huntington's disease may have reduced glucose metabolism in the caudate nuclei. We used positron emission tomography and [18F]fluorodeoxyglucose to study cerebral glucose metabolism in 95 subjects: 58 clinically asymptomatic (chorea-free) subjects at risk for Huntington's disease, 10 symptomatic patients with the disease, and 27 controls. All the symptomatic patients had marked reductions in caudate glucose metabolism. Despite a normal structural appearance on computed tomography, cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
105
1
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(115 citation statements)
references
References 39 publications
7
105
1
2
Order By: Relevance
“…This study showed significant hypometabolism in the caudate nucleus of gene mutation carriers as compared with mutation-negative subjects [9]. These first discoveries were followed by several years of relevant scientific research activity on HD which confirmed the preliminary reports and showed a significant relationship between striatal and cortical hypometabolism and motor impairment progression and cognitive changes [10][11][12]. Hayden et al found significant caudate nucleus hypometabolism in a cohort of mutation-positive subjects with no signs of cortical or striatal atrophy [13], and later Ciarmiello et al found that striatal hypometabolism is significantly correlated with the estimated age at onset [14].…”
supporting
confidence: 79%
“…This study showed significant hypometabolism in the caudate nucleus of gene mutation carriers as compared with mutation-negative subjects [9]. These first discoveries were followed by several years of relevant scientific research activity on HD which confirmed the preliminary reports and showed a significant relationship between striatal and cortical hypometabolism and motor impairment progression and cognitive changes [10][11][12]. Hayden et al found significant caudate nucleus hypometabolism in a cohort of mutation-positive subjects with no signs of cortical or striatal atrophy [13], and later Ciarmiello et al found that striatal hypometabolism is significantly correlated with the estimated age at onset [14].…”
supporting
confidence: 79%
“…These initial observations were confirmed by a number of other studies where alterations in striatal glucose metabolism were seen in early or presymptomatic HD patients [97,98]. However, a decrease in striatal glucose consumption in at-risk patients was not always observed [99]. Moreover, it is worth noting that for several reasons mainly associated with ethical considerations, such studies may be confounded by the fact that the patients may have to take medications that most of the time compete competitively with the radiotracer used (for a review, see [100]).…”
Section: Applications Of Pet In Neurodegenerative Statessupporting
confidence: 62%
“…While this patient, who is "at risk" of developing Huntington's disease, cannot strictly be considered to be pre symptomatic be cause she exhibits some affective symptoms, it is of A 8 interest to note that she shows similar appearance to that seen in established Huntington's disease. It is likely that HM-PAO is able to demonstrate pre symptomatic involvement of the caudate nucleus before any structural change is evident with X-ray CT or MRI, in a similar way that PET scanning using fluorodeoxyglucose has been shown to (Mazziotta et al, 1987).…”
Section: Huntington's Diseasementioning
confidence: 86%